2013
DOI: 10.1123/ijatt.18.1.25
|View full text |Cite
|
Sign up to set email alerts
|

Scapulothoracic Muscle Activation on Stable and Unstable Support Surfaces

Abstract: Activation of the upper trapezius, lower trapezius, serratus anterior, and triceps brachii muscles was measured, while center of pressure excursion beneath the hands was simultaneously monitored, during the performance of a push-up exercise on both a stable and an unstable base of support. The activation levels of all muscles were significantly greater for the unstable support surface when compared to those for a stable support surface (p < 0.05). A negative correlation was found between activation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…The dual-wall pushup plus exercise also produces a compression force that corrects the abnormal scapular position. Athletes and patients with shoulder injuries should perform appropriate, effective exercises to strengthen the shoulder muscles to prevent shoulder impairment and improve performance 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The dual-wall pushup plus exercise also produces a compression force that corrects the abnormal scapular position. Athletes and patients with shoulder injuries should perform appropriate, effective exercises to strengthen the shoulder muscles to prevent shoulder impairment and improve performance 9 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Only data from healthy participants, who had not undergone therapeutic intervention prior to the evaluation, were included. Regarding EMG variables, 20 studies reported only %MVIC [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], one study reported only muscle activation ratios [42], and eight studies measured both variables [7,[11][12][13][43][44][45][46]. All the investigations evaluated the UT EMG activity, 13 studies measured MT EMG activity [7,11,13,22,26,30,32,[36][37][38]40,41,46], and 21 measured the LT EMG activity [7,11-13,22,23,25-30, 32,36-41,44,46].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The exercises analyzed in the articles were the Push Up, Scap Protraction, Pull Up, Press Up, and Plank and Wall Press, with different variations of each one. Fourteen studies evaluated the Push Up exercise and its variations [7,11,12,[24][25][26][28][29][30][31][32]41,42,45], nine studies evaluated the Scap Protraction exercise and its variations [7,13,25,27,33,34,36,43,44], five studies evaluated the Pull Up and its variations [7,37,38,40,46], two studies evaluated the Press Up [13,22], four studies evaluated the Plank and its variations [23,26,35,39], and three studies evaluated the Wall Press and its variations [24,36,43]. Fourteen studies used unstable surfaces as an exercise variation (e.g.…”
Section: Summary Of Activation Ratios and Exercisesmentioning
confidence: 99%
See 2 more Smart Citations